Diagnosis and Progression of Rectal Signet Ring Cell Carcinoma in a 15 Year Old Lebanese Boy: A Case Report - Farhat, Mohammad; Abtar, Houssam; Shibli, Abbass; Dika, Zakaria; Diab, Moustafa; Taha, Alaa; Hijazi, Mariam; Moussawi, Zahraa (International Journal of Clinical Research, 2023)
Introduction: Colorectal cancer (CRC) is a rare entity in children and adolescents compared to adults. In the young, it is mostly detected in the right and transverse parts of the colon. Among the variants of CRC are the uncommon Signet Ring Cell Carcinoma (SRCC) which has a late presentation and pessimistic prognosis. Patients are asymptomatic for a long time and suddenly develop changes in bowel habits or obstruction. Case Report: A 15-year-old boy with no known health issues presented with recent rectorrhagia and weight loss. He was stable but pale with abdominal tenderness and no rectal mass on digital rectal examination (DRE). Colonoscopy unveiled a 13 centimeters segment of circumferential ulcerated blackish mucosa extending from the upper rectum to the rectosigmoid junction. Pathology studies revealed SRCC of the rectum and sigmoid. Metastatic workup showed rectosigmoid wall thickening and denoted the tumor a stage IV with ascites and intraperitoneal implants. Palliative treatment with chemotherapy was initiated, and a follow-up CT was done later to assess disease progression and response to treatment. The disease had worsened and the patient deteriorated. Conclusion: In children, colorectal SRCC is scarce and usually presents at a late stage due to the lack of characteristic symptoms and findings. It is then usually missed by physicians and not considered in the differential thus delaying the diagnosis and rendering the prognosis poorer. To improve the outcome, pediatricians ought to keep CRC in mind when facing obstructive symptoms or refractory abdominal pain.